Integration of Theravada Buddhist Philosophy Principles to Encourage Duty Performance of Officials in Bangkok Metropolitan Administration - Chaiket, Phra Ananphong Santesako; Ponsen, Kitsuchin (Journal of Dhamma for Life, 2026)
This study aimed to: (1) to study the performance of duties of Bangkok Metropolitan Administration officials; (2) to examine Theravāda Buddhist philosophy, particularly the Five Precepts, that can be applied to promote the performance of duties of Bangkok Metropolitan Administration officials; (3) to integrate Theravāda Buddhist principles with the performance of duties of Bangkok Metropolitan Administration officials; and (4) to propose an integrated model applying Theravāda Buddhist principles to promote the performance of duties of Bangkok Metropolitan Administration officials. This study employed a qualitative research methodology. Data were collected from relevant documents, concepts, theories, and previous research, as well as through fieldwork involving three groups of 15 key informants: five Buddhist and philosophical scholars, five Bangkok Metropolitan Administration officials, and five service recipients of Bangkok Metropolitan Administration officials. The research instrument was a structured in-depth interview protocol, which was examined for content validity by experts prior to data collection. The researcher conducted the interviews personally, and the data were analyzed through content analysis and systematic data synthesis. The findings revealed that the performance of duties of Bangkok Metropolitan Administration officials should emphasize responsibility in three dimensions: self-management, people management, and work management. There is also a need to strengthen morality, ethics, and consciousness in the performance of official duties. The Five Precepts refraining from killing, stealing, sexual misconduct, false speech, and intoxicants can be applied as a moral framework for regulating behavior and promoting officials’ responsibility toward themselves, others, and their duties. Such integration leads to the “3R Model,” in which the Five Precepts serve as the moral foundation and are connected to three dimensions of responsibility: self-management, people management, and work management. This model represents a process of moral development from internal cultivation to external practice, ultimately contributing to good governance, transparency, credibility, and sustainable efficiency in the performance of duties of Bangkok Metropolitan Administration officials.